THE EFFECTIVENESS OF HEALTH EDUCATION THROUGH POP-UP BOOKS AND POCKET BOOKS ON THE LEVELS OF DENTAL AND MOUTH HYGIENE IN SCHOOL-AGE CHILDREN - Melia Hayatun Nufus; Mariyam Mariyam; Nur Khamilatusy Sholekhah (Universitas Muhammadiyah Semarang, 2023)
Background: Efforts to maintain healthy teeth and mouth require special attention, especially in school-age children. Data from the Kedungmundu Health Center shows 9,491 students and 3,338 students who need treatment with a percentage of 35.37%. This is minimized by holding counseling or health education through interesting media for children. Media that has a good effectiveness value is the media pop-up book and pocket book.Method: This type of experimental research uses a nonequivalent control group design. The sample in the study were 23 students with pop-up book media and 23 students with pocket books at SD Negeri Kedungmundu, who underwent an OHI-S examination and received counseling interventions with pop-up book media and pocket books with material on maintaining oral hygiene.Result: Counseling using pop-up books and pocket books obtained a significant value of 0.000 (<0.005), which means that there was a difference before and after the intervention was given. The OHI-S score shows that the majority have a good category after being given the pocket book and pop-up book intervention.Conclusion: Counseling with pop-up book media is more effective than pocket book media on the level of dental and oral hygiene in school-age children.